Examining the Personal and Perceived Organizational Characteristics Associated With Juvenile Probation Staff Job Satisfaction - Krupa, Julie M. (Criminal justice and behavior, 2021)
Satisfied employees are essential to an organization, as they are often the primary means for meeting organizational needs. Job satisfaction is particularly important among criminal justice agencies, specifically probation agencies that largely rely on personnel for the supervision and rehabilitation of individuals. Yet, the correlates of job satisfaction among juvenile probation staff are largely unknown. Following organizational climate theory, the current study utilizes baseline data from the Juvenile Justice–Translational Research on Adolescents in the Legal System (JJ-TRIALS) initiative, a project conducted in seven states with 36 participating juvenile probation agencies. Factor analysis and structural equation modeling were utilized to examine the latent structure of organizational characteristics and potential mediating effects. Regression analyses were utilized to examine the direct relationship between job satisfaction and personal and organizational factors. Results highlight the importance of workplace factors and suggest efforts toward improving job satisfaction should focus on the improvement of organizational characteristics.